2006
DOI: 10.3748/wjg.v12.i40.6464
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of dextran sodium sulphate induced colitis in matrix metalloproteinase-9 deficient mice

Abstract: We conclude that DSS induced colitis is markedly attenuated in animals lacking MMP-9. This suggests that intestinal injury induced by DSS is modulated by MMP-9 and that inhibition of this gelatinase may reduce inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 39 publications
4
86
3
4
Order By: Relevance
“…Attenuation of the DSS-induced colitis in MMP-9-deficient mice has been reported previously (44). To validate these findings, we compared the induction of experimental colitis in WT and MMP-9 Ϫ/Ϫ mice; we found that the severity of experimental colitis after 7 days of oral administration of 3% DSS was significantly lower in MMP-9 Ϫ/Ϫ mice compared with the WT mice.…”
Section: Dss-induced Epithelial Permeability Is Attenuated In Mmp-9supporting
confidence: 71%
See 1 more Smart Citation
“…Attenuation of the DSS-induced colitis in MMP-9-deficient mice has been reported previously (44). To validate these findings, we compared the induction of experimental colitis in WT and MMP-9 Ϫ/Ϫ mice; we found that the severity of experimental colitis after 7 days of oral administration of 3% DSS was significantly lower in MMP-9 Ϫ/Ϫ mice compared with the WT mice.…”
Section: Dss-induced Epithelial Permeability Is Attenuated In Mmp-9supporting
confidence: 71%
“…MMP-9 levels in colonic tissue were found to be elevated in a rat models of chemically induced dextran sodium sulfate (DSS) colitis and treatment with a synthetic inhibitor of MMPs (CGS-27023-A) attenuated the DSS-induced colitis (30,31). Furthermore, the DSS and TNBS colitis as well as Salmonella typhimurium-induced enterocolitis were attenuated in MMP-9 Ϫ/Ϫ mice (13,35,44). In a double knockout study, MMP-9 has been shown to have overriding effect on the protective role of MMP-2 in mediating tissue damage during experimental colitis (13).…”
mentioning
confidence: 99%
“…For instance, the sex of the host is known to be correlated to differences in the immune responses of males and females to inflammatory stimuli [38][39][40]. According to our experiences (Prof. Britta Siegmund, Charité Berlin; personal communication) male mice (as used in [35]) might be more resistant to colitis induction by DSS as compared to female animals (in our study) whereas mice younger than 8 weeks of age (as used in [36]) are more susceptible to acute DSS colitis as compared to 3-month-old animals (in the presented study). Furthermore, the important role of the host microbiota composition in initiating, mediating, and perpetuating acute and chronic intestinal inflammation in mice and men is of current debate and highlighted by a plethora of recent studies [41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 50%
“…MMP-9-deficient mice were shown to be protected from acute colitis induced either by DSS [34,35] or by Salmonella Typhimurium [34]. Studies with bone marrow chimera revealed that MMP-2 and MMP-9 derived from epithelial but not immune cells, mediated colonic inflammation [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…The studies published so far have confirmed the overexpression of MMPs, including MMP-3 and -9, both in ulcerative colitis and in Crohn's disease (CD). Alterations of MMPs activity depending on the degree of disease exacerbation have been observed in animal models with induced bowel inflammation [11,12]. Elevated concentrations of MMPs have also been noted in biopsy specimens collected from inflamed fragments of the alimentary tract [1,2,13,14].…”
Section: Discussionmentioning
confidence: 99%